David Ben-Gurion and the Foundation of Israeli Democracy - Kedar, Nir (Book collections on Project MUSE., 2021)
"In David Ben-Gurion and the Foundation of Israeli Democracy, Nir Kedar offers a poignant study of the primary national founder of the State of Israel and the first prime minister of Israel. Kedar provides an explication of the making of Israeli democracy in terms of its institutional-legal structures and social-cultural underpinnings. David Ben-Gurion and the Foundation of Israeli Democracy connects the formal structures of democracy to the fundamental principles that they were constructed to serve-human freedom and dignity"--